Ekologi Sosial dalam Perspektif Hadis - Rizky Aula; Sholahuddin Al Ayubi (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2025)
This study examines social ecology from the perspective of hadith science ('ulum al-hadith), focusing on methodological analysis of prophetic traditions related to environmental and social issues. Using hadith criticism methodology, this research analyzes the authenticity, context, and semantic dimensions of ecological hadiths to construct a comprehensive framework of Islamic environmental ethics. The study applies classical hadith evaluation criteria including sanad analysis, matn criticism, and contextual interpretation to examine how prophetic traditions address the intersection of social and ecological concerns. Findings indicate that authentic hadiths provide a robust foundation for social ecological principles, with particular emphasis on stewardship (khilafah), balance (mizan), and distributive justice in resource management. This research contributes to the development of hadith-based environmental jurisprudence and offers methodologically sound approaches to understanding Islamic ecological ethics.